DNA tetrahedral scaffold-corbelled 3D DNAzyme walker for electrochemiluminescent aflatoxin B1 detection. (1st May 2023) - Li, Zongbing; Xu, Huanwen; Zhang, Zifeng; Miao, Xiangmin
Highlights: An in situ quenching ECL biosensor was designed for AFB1 detection. DNA tetrahedral scaffold corbelled 3D DNAzyme walker achieved an efficient amplification. A detection limit of 0.58 fg/mL was obtained for AFB1 detection. Sensor could be built in the arbitrary fields of target assays through replacing the aptamer. Abstract: The reaction efficiency of surface-based DNA walker can directly affect the properties of a biosensor. Herein, three-dimensional (3D) DNAzyme walker were first fixed on the top of DNA tetrahedral scaffold to improve the immobilization efficiency. Ferrocene (Fc) that labeled at substrate strand ends effectively quenched the electrochemiluminescence (ECL) signal of Ru(bpy)2 (cpaphen) 2+, yielding the sensor in a "signal-off" state. Upon the addition of aflatoxin B1 (AFB1 ), 3D DNAzyme walker was activated and fueled by Na +, accordingly releasing Fc and recovering the ECL signal of Ru(bpy)2 (cpaphen) 2+ . Due to the high movement efficiency of such 3D DNAzyme walker, ultrasensitive detection of AFB1 was achieved in the range of 1.0 fg mL −1 –10 ng mL −1, with a detection limit of 0.58 fg mL −1 . Moreover, satisfactory results were obtained while detecting AFB1 in corn and peanut samples, suggesting it has a potential application in food safety analysis.